Autophagy activators stimulate the removal of advanced glycation end products in human keratinocytes. (18th June 2020) - Laughlin, T.; Tan, Y.; Jarrold, B.; Chen, J.; Li, L.; Fang, B.; Zhao, W.; Tamura, M.; Matsubara, A.; Deng, G.; Wang, X.; Hakozaki, T.
Abstract: Background: The accumulation of advanced glycation end products (AGEs) can impact cellular homoeostasis and protein structure, thus is implicated in numerous skin conditions including yellow, dull appearance. AGE formation is irreversible; thus, understanding of the recycling process of AGEs in the skin is critical for addressing skin appearance conditions. Objective: To determine whether (i) accumulation of AGEs occurs in dull appearance group among young population (age 20–29) (ii) in vitro autophagy stimulation results in reduction of AGEs in keratinocytes. Methods: Facial cheek biopsies were collected from Chinese women (age 20–50) exhibiting either dull or non‐dull appearing skin. Histological assessment of glycation was performed for representative subjects among the 20–29 years sub‐group by immunofluorescence staining of AGEs. LC‐MS methods and keratinocyte cell culture were used to assess impact of autophagy modulators and skin care materials on carboxymethyl lysine (CML) amount, a representative AGE. Results: Notable amounts of AGEs were observed in the epidermal samples among young females. Interestingly, the amount of AGEs was significantly higher among the dull skin appearance group. Treatment of keratinocytes with glyceraldehyde (GLA) enhanced CML in the cells, and postglycation treatment with autophagy activators reduced CML. Two skin care materials, Nymphaea alba flower extract (a.k.a. white water lily extract) and sucrose dilaurate, were identified based from in vitro autophagy activation and found to reduce CML in keratinocytes. Conclusion: We found AGEs accumulate in the facial epidermis even among young people, correlating to a yellow and dull appearance. We also demonstrated in vitro activation of autophagy can reduce AGEs in keratinocytes, and autophagy activating skin care materials, N. alba flower extract and sucrose dilaurate, also reduce AGEs in the keratinocyte in vitro model. These data suggest epidermal AGEs contribute to the dull skin appearance, and autophagy activators may provide an effective solution to improve dull appearance by removing and recycling the accumulated glycation in the skin.